The Effect of the Regional “Income Tax Withholding Allowance” and “Social Security Premium Support” Programmes on Labour Outcomes in Turkey - Giovanis, Eleftherios; Ozdamar, Oznur; Akilotu, Eda (Review of Middle East economics and finance, 2021)
This paper examines the employment effects of the “Income tax withholding allowance” and “Social security premium support” programmes implemented in Turkey in 2012. The programmes aim to provide incentives to firms and generate employment opportunities for groups in targeted regions in the Eastern part of Turkey. The analysis relies on detailed micro-level data derived by the Household Labour Force Survey in 2008–2016. We apply the difference-in-differences (DID) method, and we use as treated subjects the respondents located in the regions affected by the policy. Moreover, we propose the propensity score matching approach within the DID framework to reduce the possible selection bias. The findings show a positive impact of the programme on employment, wages, the number of working hours and labour force participation, but we find a negative effect on the probability of being employed in a permanent job for the treated group.